A new skull of Megazostrodon (Mammalia, Triconodonta) from the Elliot Formation (Lower Jurassic) of Southern Africa - Gow, Chris E (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1986)
A skull of Megazostrodon with atlas and axis in articulation is described. The dental formula is 14/4 C 1/1 Pm 5/5 M 5/5. Tooth wear is more advanced than in the type specimen and the lower molar series contains evidence of tooth replacement. The braincase differs remarkably from that of Morganucodon, the only contemporaneous triconodont in which the skull is adequately known. The lower jaw has an angular process similar to that of Dinnetherium. The earliest triconodonts appear to represent a modest radiation following the attainment of mammalian status.
Keywords: atlas; axis; dental formula; braincase; Morganucodon